2016
DOI: 10.1371/journal.pone.0168406
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Long Non-Coding RNA UCA1 Increases the Tamoxifen Sensitivity of Breast Cancer Cells through Inhibition of Wnt/β-Catenin Pathway

Abstract: Acquired resistance to tamoxifen remains a major obstacle in breast cancer (BC) treatment, since the underlying mechanism has not been fully elucidated. The long non-coding RNA (lncRNA) urothelial carcinoma-associated 1 (UCA1) has been recently shown to be dysregulated and plays important roles in progression of breast cancer. In the present study, we aimed to investigate the biological role and clinical significance of UCA1 in BC drug resistance. Hence, we used quantitative PCR assay to evaluate the UCA1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 27 publications
(30 reference statements)
0
95
0
1
Order By: Relevance
“…Surprisingly, treatment of the Wnt signalling pathway agonist Wnt3a in MCF7 cells led to tamoxifen resistance, while treatment of the Wnt signalling pathway inhibitor IWP‐2 restored the sensitivity of MCF7 cells to tamoxifen, suggesting that an increase in the number of breast cancer stem cells is associated with activation of the Wnt signalling pathway. In addition, inhibition of the long non‐coding RNA UCA1 in MCF7 and T47D cells resulted in reduced activity of the Wnt signalling pathway accompanied by increased tamoxifen sensitivity . Overall, these studies show that activation of the Wnt signalling pathway plays an important role in the occurrence and development of tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Surprisingly, treatment of the Wnt signalling pathway agonist Wnt3a in MCF7 cells led to tamoxifen resistance, while treatment of the Wnt signalling pathway inhibitor IWP‐2 restored the sensitivity of MCF7 cells to tamoxifen, suggesting that an increase in the number of breast cancer stem cells is associated with activation of the Wnt signalling pathway. In addition, inhibition of the long non‐coding RNA UCA1 in MCF7 and T47D cells resulted in reduced activity of the Wnt signalling pathway accompanied by increased tamoxifen sensitivity . Overall, these studies show that activation of the Wnt signalling pathway plays an important role in the occurrence and development of tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, inhibition of the long non-coding RNA UCA1 in MCF7 and T47D cells resulted in reduced activity of the Wnt signalling pathway accompanied by increased tamoxifen sensitivity. 29 Overall, these studies show that activation of the Wnt signalling pathway plays an important role in the occurrence and development of tamoxifen resistance. Contrary to the previous study that CRB3 knockout mice displayed high levels of cytoplasmic b-catenin in the intestine, which indicates a low activity of the Wnt signalling pathway, 30 we found that CRB3 overexpression inhibited the Wnt signalling pathway, which led to decreased expression of downstream genes (CD44 and cMyc) and cancer stem cell factors (OCT4 and NANOG), and that these genes were up-regulated when cells acquired tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 90%
“…Tamoxifen treatment up-regulated expression of UCA1 in breast cancer cells through a miR-18a-HIF1a feedback loop [110]. The overexpression of UCA1 conferred tamoxifen resistance by increasing the activity of Wntb-catenin signaling, which was accompanied by a decrease of miR-18a, an important modulator of cell cycle proteins [111,112]. Knockdown of UCA1 increased apoptosis upon tamoxifen treatment accompanied by an increase of cleaved caspase-3 and reduction in p-AKT and p-mechanistic target of rapamycin [113].…”
Section: Breast Cancermentioning
confidence: 99%
“…In addition, the knockdown of CCAT2 repressed both the levels of cytoplasmic and nuclear β‐catenin, suggesting that CCAT2 regulates the transcriptional level of β‐catenin and its expression is associated with the development of breast tumor. Furthermore, the overexpression of UCA1 elevates invasion of breast cancer cells via activating the Wnt/β‐catenin signaling pathway, which demonstrates that UCA1 has the ability to increase the activity of Wnt/β‐catenin signaling by enhancing the nuclear translocation of β‐catenin (H. Liu et al, 2016). Functionally, the UCA1 knockdown suppresses the protein levels of β‐catenin and results in decreased transcription of the downstream genes of β‐catenin, including cyclin D1 and matrix metalloproteinase‐7 (MMP‐7).…”
Section: Crosstalk Between Various Signaling Pathways and Lncrnasmentioning
confidence: 99%